The Effect of Plug Height and Inflow Rate on Water Flow Characteristics in Furrow Irrigation - Yu, Juan; Liu, Keyao; Li, Anbin; Yang, Mingfei; Gao, Xiaodong; Zhao, Xining; Cai, Yaohui (Agronomy (Basel), 2022)
Despite its wide application across arid land types, furrow irrigation is often associated with numerous environmental problems related to deep percolation, runoff, and soil erosion. In this study, a straightforward approach was proposed to achieve higher uniformity and reduce erosion. Here, the impacts that a moveable “plug” has on the behavior of irrigation water in the furrow were simulated using FLOW-3D and HYDRUS-2D, where three plug heights and two flow rates were set. The effect of inflow rate and plug height on the water advance, water level, cumulative infiltration in the furrow, and uniformity coefficient was determined. Results indicate that the plug was able to slow water velocity by approximately 60% in the furrow and increase the furrow advance time by 3–4 times; the water level was increased by nearly 10 cm compared with no plug. Moreover, an irrigation uniformity range of 90.18–99.22% was associated with this plugging. The addition of a plug in the furrow irrigation practices for smallholder farmers in developing countries demonstrates great potential in reducing the probability of erosion under large slopes and can effectively improve irrigation uniformity.